Mochila tática impermeável para a prática de trekking e hiking - Castro Neto, Paulo Aristeu de Souto (2019)
The project in question addresses the execution of a waterproof tactical backpack for trekking and hiking for people of medium and tall stature. Adventure sports such as trekking and hiking need a fundamental equipment, the backpack, which facilitates the transport of extra equipment, such as: food, hydration cartridge, blade, lantern, mat, tent, extra clothes, among others, enabling the wearer. stay for 1 to 3 days on the trail, as well as take short walks. One of the main focuses of these practitioners is to find backpacks that are comfortable and sturdy, as well as a good internal division that has possibilities of external modularity to insert other equipment. Throughout this project it becomes possible to observe the analyzes developed, as well as data surveys and surveys to identify the main components of a tactical backpack, so that the product in question would add to the national tactical backpack market, bringing more an option geared towards the practice of Trekking and Hiking sports. The Bravo backpack aims to address the main needs of internal and external organization for the wearer, as well as bring comfort and safety of use. The backpack has 55L of internal capacity and can reduce this capacity to 35L with the side compression straps, thus characterizing and reinforcing its proposal to be applied in both sports.